2016
DOI: 10.1556/2060.103.2016.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of fumonisin B1and T-2 individually and in combination affects hepatic total and mitochondrial membrane lipid profile of rabbits

Abstract: Weaned rabbits were fed diets contaminated with 2 mg/kg diet T-2 toxin alone, or 10 mg/kg diet fumonisin B 1 (FB 1 ) alone, and both toxins in combination (2 + 10 mg/kg, respectively) compared to a toxin-free control diet. Samplings were performed after 4 weeks (blood and liver). Bodyweight of T-2-fed group was lower after 4 weeks; the liver weight was increased dramatically (threefold of control). Liver total phospholipids (PLs) provided slight alterations in the fatty acid (FA) composition; all three toxin-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The Sa/So ratio is a pertinent marker of exposure to FB1 in the liver, which reveals an accumulation of sphinganine due to inhibition of ceramide synthase proteins involved in ceramide de novo synthesis. Several groups have already reported an increase in this ratio in animals exposed to FB1 …”
Section: Resultsmentioning
confidence: 88%
“…The Sa/So ratio is a pertinent marker of exposure to FB1 in the liver, which reveals an accumulation of sphinganine due to inhibition of ceramide synthase proteins involved in ceramide de novo synthesis. Several groups have already reported an increase in this ratio in animals exposed to FB1 …”
Section: Resultsmentioning
confidence: 88%
“…Since MDA results from end-phase lipid peroxidation, it seems that hydrogen free radicals attacked tissue lipids, as already published in an earlier study in rats [ 16 ]. Interestingly, a lower dose for a longer exposure period (10 ppm for 14 days) failed to induce MDA increment in rabbits [ 17 ], referring to a possible dose-dependent effect of FB 1 onward in vivo lipid peroxidation. It is rather interesting that initiation-phase lipid peroxidation, as assessed by the determination of conjugated dienes and trienes, was not increased in the liver by any of the treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier studies, high dose (50 ppm), but short exposure (5 days) in rats depleted hepatic GSH and induced lipid peroxidation (malondialdehyde, MDA), without activating the enzymatic defense [ 16 ]. In rabbits, the hepatic lipid peroxidation was minimal, as assessed by GSH, GSHPx and MDA, after feeding 10 ppm FB 1 for 4 weeks [ 17 ]. The nature of FB 1 -induced oxidative stress is likewise acute.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence also suggests that mitochondria are important molecular targets for FB 1 (Arumugam et al, 2019; Bionda, Portoukalian, Schmitt, Rodriguez‐Lafrasse, & Ardail, 2004; Domijan & Abramov, 2011). A recent study suggests that FB 1 could be rapidly absorbed by mitochondria isolated from rabbit hepatocytes without drastic membrane disruption (Szabó et al, 2016); however, changes to the normal morphology of mitochondria were observed in other studies (Ciarlo et al, 2010; Kroesen et al, 2001). Mitochondria play integral roles in energy production, calcium ions (Ca 2+ ) and redox homeostasis, as well as regulation of apoptosis.…”
Section: Introductionmentioning
confidence: 94%